AlPd15B7: a new superconducting cage-compound with an anti-Yb3Rh4Sn13-type of structure. Issue 9 (2nd February 2016) - Zheng, Qiang; Schnelle, Walter; Prots, Yurii; Bobnar, Matej; Burkhardt, Ulrich; Leithe-Jasper, Andreas; Gumeniuk, Roman
Abstract : AlPd15 B7 is the first boride with a crystal structure comprising the framework of the Remeika phases. Abstract : A new intermetallic compound AlPd15 B7 was synthesized by arc-melting the stoichiometric mixture of the elements. Single crystal X-ray diffraction data of ternary metal-rich boride reveal a new type of structure with the space group Ia 3̄ d and the lattice parameter a = 16.4466(3) Å. It adopts a filled anti -Yb3 Rh4 Sn13 -type structure, where the positions corresponding to 3Yb, 4Rh and 13Sn atoms are occupied by 3Pd, 4B, and 1Al + 12 Pd, respectively and 3B additionally at interstitial sites. Magnetic susceptibility, electrical resistivity, and specific heat measurements reveal bulk superconductivity with a critical temperature T c ≈ 2.9 K. Electronic structure calculations show that Pd 4d and B 2p states dominate the density of states (DOS) at the Fermi level E F .